2018
DOI: 10.1002/jbm.b.34106
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine/cysteine surface modified hemocompatible poly(vinylidene fluoride) hollow fiber membranes for hemodialysis

Abstract: Membrane surface design is significant for the development and application of synthetic polymer hemodialysis membranes. In this study, the influence of zwitterionic cysteine on poly(vinylidene fluoride) (PVDF) hollow fiber membrane was investigated. The polydopamine layer was formed through dopamine self-polymerization on PVDF membrane surface, and then cysteine was covalent grafted onto the layer to improve the anti-biofouling property and hemocompatibility. The elementary composition of membrane surfaces was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Grafting polymer onto the surface by chemical methods is the most common approaches in material modification. Initially, the researchers conducted a series of hydrophobic modification studies to reduce blood leakage, including poly (L-lactide) (PLLA), poly (choline phosphate methacrylate) copolymers, and poly (2-methoxyethyl acrylate) (PMEA) [67]; however, hydrophobic surface can aggravate protein adhesion fouling [68]. Hydrophilic modification is an effective method to enhance the biocompatibility, such as polyethylene oxide (PEO) or poly (ethylene glycol) (PEG), which are employed to enhance the surface hydrophilicity of materials and achieve antifouling ability [69][70][71].…”
Section: Surface Chemical Modificationmentioning
confidence: 99%
“…Grafting polymer onto the surface by chemical methods is the most common approaches in material modification. Initially, the researchers conducted a series of hydrophobic modification studies to reduce blood leakage, including poly (L-lactide) (PLLA), poly (choline phosphate methacrylate) copolymers, and poly (2-methoxyethyl acrylate) (PMEA) [67]; however, hydrophobic surface can aggravate protein adhesion fouling [68]. Hydrophilic modification is an effective method to enhance the biocompatibility, such as polyethylene oxide (PEO) or poly (ethylene glycol) (PEG), which are employed to enhance the surface hydrophilicity of materials and achieve antifouling ability [69][70][71].…”
Section: Surface Chemical Modificationmentioning
confidence: 99%
“…Furthermore, helpful methods to eliminate fouling can be, for example, heat and plasma treatment [ 4 , 34 , 35 , 36 , 37 ], coating or grafting of hydrophilic polymers onto membranes’ surfaces [ 33 , 35 , 38 , 39 , 40 , 41 , 42 , 43 ], or through the addition of hydrophilic pore precursors to a polymer solution or other admixture like nanoparticles [ 6 , 19 , 25 , 44 , 45 , 46 , 47 , 48 ]. The modification could be influenced by an increase of the hydraulic permeability and/or the hydrophilicity of membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The co-deposition of PDA and the ZW structure of cysteine on polyvinylidene fluoride (PVDF) hollow fiber membranes was suggested by An et al 14 Methacrylate ZW-PDA modification through a one-step co-deposition was also reported by Shahkaramipour et al 21 for wastewater treatment applications. The methodology introduced sulfobetaine methacrylate (SBMA)-PDA immobilized on a polyether sulfone (PES) ultrafiltration membrane.…”
mentioning
confidence: 98%
“…As an alternative to bulk casting solution modification, PDA can be coated on polymeric structure surfaces. 14 Several membrane materials and different membrane geometries can be enhanced with such a middle adhesive structure; indeed, DA-assisted immobilization of different structures has been reported for a variety of different polymers and zwitterionic (ZW) structures. [15][16][17][18] The mechanism through which the adhesive nature of DA works is as follows, amino and catechol groups on the surface of the DA monomers oxypolymerize to PDA within a basic environment and in the absence of air.…”
mentioning
confidence: 99%